2020
DOI: 10.1073/pnas.1913737117
|View full text |Cite
|
Sign up to set email alerts
|

Spin-labeled nanobodies as protein conformational reporters for electron paramagnetic resonance in cellular membranes

Abstract: Nanobodies are emerging tools in a variety of fields such as structural biology, cell imaging, and drug discovery. Here we pioneer the use of their spin-labeled variants as reporters of conformational dynamics of membrane proteins using DEER spectroscopy. At the example of the bacterial ABC transporter TM287/288, we show that two gadolinium-labeled nanobodies allow us to quantify, via analysis of the modulation depth of DEER traces, the fraction of transporters adopting the outward-facing state under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…To determine the location of the substrate we made use of Gd(III)-NO measurements (24,35,36), between Gd(III) singly labeled MdfA and a NO labeled TPP analog, mito-TEMPO. The choice of employing Gd(III)-NO measurements, as opposed to the more standard NO-NO distance measurements allowed us to work under conditions of excess substrate with minimal interferences from the unbound substrate and avoid potential contributions of substrate-substrate distances to the distance distributions because the NO signal is saturated under the measurement conditions optimized for Gd(III) detection (28).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the location of the substrate we made use of Gd(III)-NO measurements (24,35,36), between Gd(III) singly labeled MdfA and a NO labeled TPP analog, mito-TEMPO. The choice of employing Gd(III)-NO measurements, as opposed to the more standard NO-NO distance measurements allowed us to work under conditions of excess substrate with minimal interferences from the unbound substrate and avoid potential contributions of substrate-substrate distances to the distance distributions because the NO signal is saturated under the measurement conditions optimized for Gd(III) detection (28).…”
Section: Discussionmentioning
confidence: 99%
“…In our recently published nanobody‐assisted EPR study [75], we used a ‘cocktail’ of a state‐ and a non‐state‐specific nanobody to probe the conformation of the heterodimeric exporter TM287/288 in the membrane environment of ISOVs using DEER spectroscopy. Due to the specificity of the nanobodies, only TM287/288 was targeted in the crowded membrane environment of the ISOVs.…”
Section: Nanobody‐assisted In Situ Eprmentioning
confidence: 99%
“…The term orthogonal refers to spin labels that are spectroscopically distinguishable from each other and that can be addressed and/or detected independently, e.g., via distinct resonance frequencies, relaxation behavior, or transition moments. Despite most spin labels being nonperfectly orthogonal, it was shown that specific interspin interactions can be addressed independently, as demonstrated by several publications on a large number of combinations of spin labels, e.g., nitroxides in combination with trityl (Shevelev et al, 2015;Joseph et al, 2016;Jassoy et al, 2017), Gd III (Lueders et al, 2011;Kaminker et al, 2012;Yulikov et al, 2012;Lueders et al, 2013;Garbuio et al, 2013;Kaminker et al, 2013;Gmeiner et al, 2017a, b;Teucher et al, 2019;Shah et al, 2019;Galazzo et al, 2020), Fe III (Ezhevskaya et al, 2013;Abdullin et al, 2015;Motion et al, 2016), Cu II (Narr et al, 2002;Bode et al, 2008Bode et al, , 2009, or Mn II (Kaminker et al, 2015;Akhmetzyanov et al, 2015;. The orthogonal spin-labeling approach has also been extended to more than two orthogonal spin labels (Wu et al, 2017).…”
Section: Orthogonal Spin Labelingmentioning
confidence: 99%